2016
DOI: 10.12688/f1000research.9392.1
|View full text |Cite
|
Sign up to set email alerts
|

Biting the hand that feeds: current opinion on the interpersonal causes, correlates, and consequences of borderline personality disorder

Abstract: Borderline personality disorder (BPD) is a complex psychiatric diagnosis characterized by dysregulated behaviors, emotions, cognitions, and interpersonal relationships. In recent years, developmental psychopathologists have sought to identify early origins of BPD, with the ultimate goal of developing and providing effective preventative interventions for those at highest risk. In addition to heritable biological sensitivities, many scholars assert that environmental and interpersonal risk factors contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…In essence, BSCT suggests that emotional sensitivity broadens children’s range of adaptive responding, which is “tuned” to untoward outcomes in contexts of adversity, but favorable outcomes in contexts of enrichment. Following from this logic, BSCT theorists hypothesize that ongoing calibration of emotional and physiological stress systems occurs within parent-child relationships (e.g., Del Giudice, Ellis, & Shirtcliff, 2011), which are often compromised in families of self-injuring youth (see, e.g., Crowell, 2016). To date, there are few tests of sensitivity theories among self-injuring samples.…”
mentioning
confidence: 99%
“…In essence, BSCT suggests that emotional sensitivity broadens children’s range of adaptive responding, which is “tuned” to untoward outcomes in contexts of adversity, but favorable outcomes in contexts of enrichment. Following from this logic, BSCT theorists hypothesize that ongoing calibration of emotional and physiological stress systems occurs within parent-child relationships (e.g., Del Giudice, Ellis, & Shirtcliff, 2011), which are often compromised in families of self-injuring youth (see, e.g., Crowell, 2016). To date, there are few tests of sensitivity theories among self-injuring samples.…”
mentioning
confidence: 99%
“…To date, there are disparate, individual research studies examining the individual indicators of social connectedness and their relation to BPD (e.g., Beeney et al, 2018; Bouchard & Sabourin, 2009; Crowell, 2016; Zanarini et al, 2015). However, while there is literature examining the relationship between social connectedness indicators and BPD, the research literature in this area lacks integration.…”
Section: Social Connectednessmentioning
confidence: 99%
“…Similar approaches among men who have sex with men have shown that risky sexual behavior accompanies common symptoms of BPD [ 38 ]. Our approach follows the work of Northey et al [ 39 ] in viewing sexual implications of BPD symptomology among a non-clinical population, contributing to an emerging focus on the relational aspects of this mental illness [ 40 ].…”
Section: Introductionmentioning
confidence: 99%